2000
DOI: 10.1111/j.1346-8138.2000.tb02240.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen Planus after HBV Vaccination in a Child: A Case Report from Nepal

Abstract: Vaccination against hepatitis B virus has rarely been associated with lichen planus. We report a case of this kind in a child from Nepal. A 12-year-old boy had developed generalized itchy violaceous papules and plaques six weeks after the second dose of hepatitis B virus vaccine. Serum HBsAg and HBeAb were negative, but HBsAb was positive. New crops of generalized, similar eruptions developed after the booster dose of vaccine. All the lesions resolved within three months of systemic steroid therapy. There was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0
1

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 8 publications
2
20
0
1
Order By: Relevance
“…So wurde von mehreren Patienten berichtet, die nach aktiver Immunisierung gegen HBV innerhalb weniger Wochen lichenoide Hautveränderungen entwickelten. Seit 1990 wurden 26 Patienten mit durch Hepatitis-B-Impfung ausgelöstem Lichen ruber planus beschrieben, darunter 7 Kinder [1,10,12,17]. In den meisten Fäl-len entwickelten die Patienten 2-3 Monate nach der ersten Injektion des Impfstoffs papulöse, juckende Hautverände-rungen, die histologisch als Lichen ruber planus gesichert wurden.…”
Section: Schlüsselwörterunclassified
“…So wurde von mehreren Patienten berichtet, die nach aktiver Immunisierung gegen HBV innerhalb weniger Wochen lichenoide Hautveränderungen entwickelten. Seit 1990 wurden 26 Patienten mit durch Hepatitis-B-Impfung ausgelöstem Lichen ruber planus beschrieben, darunter 7 Kinder [1,10,12,17]. In den meisten Fäl-len entwickelten die Patienten 2-3 Monate nach der ersten Injektion des Impfstoffs papulöse, juckende Hautverände-rungen, die histologisch als Lichen ruber planus gesichert wurden.…”
Section: Schlüsselwörterunclassified
“…[13] The conditions commonly associated juvenile OLP include (1) previous history of hepatitis B vaccination; (2) liver disease and (3) genetic predisposition, as in familial LP. [14][15][16] Alterations in clinical features of adult and juvenile LP have been noticed. Several authors have reported that LP in children could exhibit atypical features, like "linear" pattern uncommon seen in adults.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, less than 20 cases of LP or lichenoid reactions following HBV vaccination with all types of vaccines (recombinant and plasma-derived) have been reported [3, 5, 10, 11, 12, 13, 14]. Given the diffusion of HBV vaccination, the incidence of postvaccine LP is low.…”
Section: Discussionmentioning
confidence: 99%
“…Since the reaction has occurred following vaccination with all types of HBV vaccines and given the diversity of these vaccines, it seems plausible that any factor common in all vaccines is a candidate causal factor. The only common constituent is the protein S fraction of the HBsAg [3, 5, 9, 10, 11, 12, 13, 14]. Based on the clinical and histological features and the time course of the postvaccine LP, it has been speculated that a T-cell-mediated, graft-versus-host-like reaction takes place.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation